KNOWLEDGE AND PRACTICE OF EXCLUSIVE BREAST FEEDING AMONG POSTNATAL MOTHERS INENUGU MUNICIPALITY OFENUGU STATE - CHUKWU, B.N.; EZEBUIRO, V. O.; UDUMA, C (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2023)
Exclusive breastfeeding was established by Nigerian government to reduce infant morbidity and mortality in Nigeria. This study determined the knowledge and practice of exclusive breastfeeding among postnatal mothers in Enugu municipality of Enugu State. Two research questions and two hypotheses were formulated to guide the study. Descriptive survey research design was employed. A sample of 200 postnatal mothers were randomly selected. Questionnaire was used to collect the data. Mean and Standard Deviation was used to answer research question 1,frequency and percentage was used to answer research question 2 while hypothesis 1 and 2 were tested using ANOVA and](2 respectively at 0.05 level of significance. Thefindings of the study revealed that postnatal mothers have positive knowledge; and practiced exclusive breastfeeding; age of postnatal mothers does not affect their knowledge in Exclusive breastfeeding; and that age of the postnatal mothers does not affect the practice of exclusive breastfeeding. It was recommended among others that postnatal mothers who exclusively breastfeed their babies should be provided with free supplements to replenish the nutrient they loose during child breastfeeding as a means to achieve safe motherhood.